ANALISA PENGARUH PERUBAHAN PANJANG CHORD DAN KETEBALAN BLADE PADA TURBIN PEMBANGKIT TENAGA ARUS DENGAN METODE CFD - Trimulyono, Andi; Andriawan, Ryan (Department of Naval Architecture - Diponegoro University, 2011)
Indonesia as an archipelagic country has territorial waters wider than the land, so the Indonesian seas provide a very large alternative energy, such as energy produced from ocean currents. This energy can produce a very large kinetic energy and environmentally friendly. During this ocean current energy generation power that has developed and patented a type of Darrieus Water Turbine propulsion and turbine vertical Axiz kobolt. In this study, using a turbine with NACA 0018 foil type, by modifying the NACA 0018 foil with changing chord length and thickness of the blade to get a big lift and drag are smaller than the foil using a standard numerical method Computational Fluid Dynamics (CFD). Single foil modified by reducing the thickness of the blade to be at 50%, 80%, 95% decline in the value of CL and the ratio CL / CD. While the modifications with the addition of a chord of 5%, 10%, 15% an increase in the value of CL and the ratio CL / CD. Based on these results the best modifications for a single foil is to increase the length of 15% chord. As for the best modification of the group for the thickness is the thickness of 95% occurred at 9.9 seconds with a maximum torque Nm Â² 1,72.10 and chord length for modification is the addition of 5% occurred in 4.3 seconds with a maximum torque of 1,84.10 Nm Â²